2016
DOI: 10.1016/j.jare.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of electrospun nanofibres of BCS II drug for enhanced dissolution and permeation across skin

Abstract: The present work reports preparation of irbesartan (IBS) loaded nanofibre mats using electrospinning technique. The prepared nanofibres were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction analysis, in vitro diffusion and ex vivo skin permeation studies. FTIR studies revealed chemical compatibility of IBS and polyvinyl pyrrolidine (PVP K-30). SEM images confirmed formation of nanofibres wherein IBS existed in amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 19 publications
2
13
1
1
Order By: Relevance
“…It has been reported that electrospun nanofibers could enhance solubility and form a transdermal patch for the biopharmaceutics classification systems II drugs with a high therapeutic efficiency and no cytotoxicity. Hydrophilic polymers with great permeation are the strength of TDDS, and several in vitro and in vivo evaluations suggest the possibility of using drug-loaded electrospun nanofibers in establishing TDDS [59].…”
Section: Therapeutics Delivery Systemsmentioning
confidence: 99%
“…It has been reported that electrospun nanofibers could enhance solubility and form a transdermal patch for the biopharmaceutics classification systems II drugs with a high therapeutic efficiency and no cytotoxicity. Hydrophilic polymers with great permeation are the strength of TDDS, and several in vitro and in vivo evaluations suggest the possibility of using drug-loaded electrospun nanofibers in establishing TDDS [59].…”
Section: Therapeutics Delivery Systemsmentioning
confidence: 99%
“…The release−permeation of Ibu from the Ibu‐loaded NR patch and Ibu‐doped PPV/NR patch was investigated next. The release−permeation characteristic of Ibu from the Ibu‐loaded NR patch and Ibu‐doped PPV/NR patch were investigated using a modified Franz diffusion cell at pH 7.4 at 37 °C for the duration of 48 h . Each patch (area 3.14 cm 2 and thickness 0.5 cm) was placed on pigskin, which was mounted on a receptor chamber of the modified Franz cell and covered on top by an anode electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Amidon et al classified drug molecules as a function of their aqueous solubility and intestinal permeability in the Biopharmaceutics Classification System (BCS) [139]. Classes II and IV in the BCS have poor solubility due to their complete dose not being possible to dissolve when ingested with a glass of water (250 ml) [140][141][142]. A great majority of new drug molecules and lead compounds are within Class II and IV, and thus present limited oral absorption, slow in vivo dissolution, and low bioavailability [141,[143][144][145].…”
Section: Technological Issues For the Formulation Of Poorly Water-solmentioning
confidence: 99%